Locally brewed alcohol induced rhabdomyolysis: A case report - Keesari Sai Sandeep Reddy; Subbiah Senthilnathan; Selvamani T.; Priyadarshini Varadaraj; Gunasekaran N. (Romanian Medical Journal)
Background. This case report aims to present an occurrence of Rhabdomyolysis following locally brewed alcohol consumption. We describe the clinical features, diagnostic evaluation, treatment, and outcomes of a patient diagnosed with rhabdomyolysis and secondary to locally made alcohol consumption. Case report. The patient, a 31-year-old male, known alcoholic since 13 years, presented with sudden-onset bilateral lower limb weakness for 4 days, h/o inability to walk, h/o leg pain for 4 days, non-progressive, no aggravating and relieving factors following alcohol consumption. Investigations revealed critically high levels of CPK, deranged renal parameters and liver parameters. Prompt intervention and mechanical hemodialysis were initiated along with administration of supportive care. The patient demonstrated gradual improvement of symptoms and renal parameters. Conclusions. This case highlights the importance of recognizing the potential muscle injury with acute kidney and liver injury following locally brewed alcohol consumption. In many villages in India locally brewed alcohol is still being consumed. Early diagnosis and prompt management are crucial for good prognostic outcome.